The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3945/ajcn.115.123786
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D concentration is inversely associated with mucosal inflammation in patients with ulcerative colitis,

Abstract: Background: Vitamin D exerts anti-inflammatory actions both in vitro and in murine models of colitis. In previous studies, we demonstrated that vitamin D protects against the development of colitis by maintaining the integrity of the intestinal mucosal barrier. Objective: We sought to evaluate whether deficient serum 25 hydroxyvitamin D [25(OH)D] concentrations are associated with increased mucosal inflammation, a loss of epithelial junctional proteins, and an increase in mucosal inflammatory cytokines in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 53 publications
3
61
1
3
Order By: Relevance
“…Destruction of barrier function is found in colitis [29] . Our results showed that the expression levels of occludin and ZO-1 protein were significantly lower ( Figure 5C, 5D) in LPSinfected Caco-2 cells than in the control Caco-2 cells.…”
Section: Geniposide-induced Amelioration Of Barrier Dysfunction In Vitromentioning
confidence: 99%
“…Destruction of barrier function is found in colitis [29] . Our results showed that the expression levels of occludin and ZO-1 protein were significantly lower ( Figure 5C, 5D) in LPSinfected Caco-2 cells than in the control Caco-2 cells.…”
Section: Geniposide-induced Amelioration Of Barrier Dysfunction In Vitromentioning
confidence: 99%
“…In patients, serum vitamin D concentrations and UC disease activity are inversely related (42). The role of vitamin D in intestinal homeostasis has been shown through regulation of autophagy (43) and tight junctions (44).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated C-reactive protein as a marker of inflammation was inversely associated with 25(OH)D deficiency in newborns born in winter–spring, supporting this seasonal effect [63]. Moreover, dysbiosis of the microbiome and susceptibility to infection can be shaped by 25(OH)D status, further illustrating the biological importance of this molecule in maintaining health [64,65]. However, translating these findings to clinical trials of 1,25(OH) 2 D 3 supplementation in infants and adults have not been promising largely due to the inconsistency among trial designs.…”
Section: Discussionmentioning
confidence: 96%